Applying the CDIO approach: One of ways to renovate Higher Education management at University of Technical Education of HCM City(UTE-HCM) - Nguyễn, Tiến Dũng (Đại học Quốc gia Thành phố Hồ Chí Minh, 2016)
The University of Technical Education in HCM City (UTE-HCM) has 21 branches and 52 programmes in 07 training areas (Enginnering Technology, Lecturer Training, Applied Arts, Computer science and Information, Business and Management, Production and Processing, Hotel-Tourism-Sports-Individual Services). The implementation of the CDIO approach to restructure current programmes has been carried out since 2008-2009 school year, and is going to complete in May this year. This Paper is going to describe UTE-HCM’s experiences in apply the CDIO approach at UTE-HCM.